Kohesi Leksikal Dalam Surah Al-Kahfi: Kajian Analisis Wacana - Nita Zakiah (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2022)
Research on lexical cohesion in surah Al Kahfi aims to be known lexical relationship between parts of the text to get cohesive structural compatibility, in terms of words in the Qur'anic verse, or between verses with other verses. The study of lexical cohesion in surah Al-Kahfi used a descriptive qualitative approach. The data collection technique used was library research to obtain data. The method used in the data analysis stage was the distributional method. Lexical cohesion in Surah Al Kahfi was proven by reiteration and collocation. Reiteration is repeating the words in the next sentence to give emphasize that the word is the object. The results of this research are that Reiteration in surah Al Kahfi in the verses 32-33 and verse 51, a synonym in the verses 30-31 and verse 54, hyponym in the verses 34-35, verses 50 and 54, metonym in the verses 9-10, and the antonym in the verses 18, 63, and 17. Collocation is based on the relationship between the words in common the fact that frequently occurs around it, or link meaning between a single word in other words in the same context, such as in verses 17 and 29